Dielectric Properties of Sol–Gel‐Derived Bi12SiO20 Thin Films. Issue 1 (26th September 2012) - Veber, Asja; Kunej, Špela; Suvorov, Danilo; Randall, C.
<x xml:space="preserve">Abstract</x> In this paper the dielectric properties of crack‐free, Bi12SiO20 thin films were investigated. The films were prepared on Pt/TiO2/SiO2/Si and corundum substrates using the sol–gel method. The formation of a pure Bi12SiO20 phase was observed at a temperature of 700°C. The Bi12SiO20 thin films, heat treated at 700°C for 1 h, had a dense microstructure with an average roughness (Ra) of 50 nm. The dielectric properties of the film were characterized by using both low‐ and microwave‐frequency measurement techniques. The low‐frequency measurements were conducted with a parallel capacitor configuration. The dielectric constant and dielectric losses were 44 and 7.5 × 10−3, respectively. The thin‐film dielectric properties at the microwave frequency were measured using the split‐post, dielectric resonator method (15 GHz) and the planar capacitor configuration (1–5 GHz). The dielectric constant and the dielectric losses measured at 15 GHz were 40 and 17 × 10−3, respectively, while the dielectric constant and the dielectric losses measured with the planar capacitor configuration were 39 and 65 × 10−3, respectively.